Lung Tissue Microbiome Is Associated With Clinical Outcomes of Idiopathic Pulmonary Fibrosis - Yoon, Hee-Young; Moon, Su-Jin; Song, Jin Woo (Frontiers in Medicine, 2021)
Background: Several studies using bronchoalveolar lavage fluid reported that lung microbial communities were associated with the development and clinical outcome of idiopathic pulmonary fibrosis (IPF). However, the microbial communities in IPF lung tissues are not well known. The aim of this study was to investigate bacterial microbial communities in lung tissues, and determine their impact on the clinical outcomes of patients with IPF. Methods: Genomic DNA extracted from lung tissues of patients with IPF (n = 20; 10 non-survivors) and age- and sex-matched controls (n = 20) was amplified using fusion primers targeting the V3 and V4 regions of the 16S RNA genes with indexing barcodes. Results: Mean age of IPF subjects was 63.3 years, and 65% were male. Alpha diversity indices did not significantly differ between IPF patients and controls, or between IPF non-survivors and survivors. The relative abundance of Lactobacillus, Pracoccus, and Akkermansia increased, whereas that of Caulobacter, Azonexus, and Undibacterium decreased in patients with IPF compared with that in the controls. A decreased relative abundance of Pelomonas, (odds ratio [OR]: 0.352, p=0.027) and Azonexus (OR: 0.013, p=0.046) was associated with a diagnosis of IPF in the multivariable logistic analysis adjusted by age and gender. Multivariable Cox analysis adjusted for age and forced vital capacity (FVC) revealed that higher relative abundance of Streptococcus (hazard ratio [HR]: 1.993, p=0.044), Sphingomonas (HR: 57.590, p=0.024), and Clostridium (HR: 37.189, p=0.038) were independently associated with IPF mortality. The relative abundance of Curvibacter (r = 0.590) and Thioprofundum (r = 0.373) correlated positively, whereas that of Anoxybacillus (r = -0.509), and Enterococcus (r = -0.593) correlated inversely with FVC. Also, the relative abundance of the Aquabacterium (r = 0.616) and Peptoniphilus (r = 0.606) genera positively correlated, whereas that of the Fusobacterium (r = -0.464), and Phycicoccus (r = -0.495) genera inversely correlated with distance during the 6-minute walking test. Conclusions: The composition of the microbiome in lung tissues differed between IPF patients and controls, and was associated with the diagnosis, mortality, and disease severity of IPF.